2004
DOI: 10.1074/jbc.m403690200
|View full text |Cite
|
Sign up to set email alerts
|

A Maternal Ahr Null Genotype Sensitizes Embryos to Chemical Teratogenesis

Abstract: The aryl hydrocarbon receptor (encoded by the Ahr locus) is a ligand-activated transcription factor that mediates the toxicology and teratology of 2,3,7,8-tetrachlorodibenzo-p-dioxin (dioxin). In an effort to understand the role of the maternal compartment in dioxin teratology, we designed a breeding strategy that allowed us to compare the teratogenic response in embryos from Ahr ؊/؊ (null) and Ahr ؉/؉ (wild-type) dams. Using this strategy, we demonstrate that embryos from the Ahr ؊/؊ dams are 5-fold more sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…Given that dioxin-induced hydronephrosis occurs at a dose approximately 10-fold lower than the dose that produces cleft palate, the screen was less sensitive for detecting loci influencing dioxin-induced hydronephrosis (Thomae et al, 2004). Although our linkage analysis suggested the potential for numerous modifiers of dioxininduced hydronephrosis, the relatively low LOD scores led us to focus on modifiers of dioxin-induced cleft palate where our screen was more sensitive.…”
Section: Discussionmentioning
confidence: 99%
“…Given that dioxin-induced hydronephrosis occurs at a dose approximately 10-fold lower than the dose that produces cleft palate, the screen was less sensitive for detecting loci influencing dioxin-induced hydronephrosis (Thomae et al, 2004). Although our linkage analysis suggested the potential for numerous modifiers of dioxininduced hydronephrosis, the relatively low LOD scores led us to focus on modifiers of dioxin-induced cleft palate where our screen was more sensitive.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal mice were obtained from timed breeding of Ahr ϩ/Ϫ female mice with Ahr Ϫ/Ϫ male mice as described previously (Thomae et al, 2004). In brief, the morning after mating was considered E0.5.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, and consistent with the hypothesis, Thomae et al (2005) reported that the addition of TGFβ3 to dioxin-exposed in vitro palatal culture restored palatal fusion. Mouse embryos from Ahr null mothers were reported to be five times more sensitive to dioxin-induced cleft palate, suggesting potential maternal effects of the AhR gene (Thomae et al, 2004).…”
Section: Genes Of Special Interests To Gene-smoking Effects On Cleft mentioning
confidence: 99%